THE EVALUATION OF THE ROLE OF THE VARIOUS TYPES OF FERTILIZERS ON THE PROCESS OF THE ACCUMULATION OF CONTENT OF NITRATES IN FORAGE CROPS - Larisa CREMENEAC (Scientific Papers Series : Management, Economic Engineering in Agriculture and Rural Development)
The purpose of the conducted researches ascertained in the evaluation of the influence of worm compost and ammonium nitrate on the accumulation of the content of nitrate in forage crops on cultivation of which these fertilizers were used. The article presents results of studies regarding to the role of worm compost and ammonium nitrate in the process of accumulation of nitrates in maize, alfalfa and fodder beet in different phenological stages of development. It was found that the use of worm compost and nitrate, as fertilizers influenced the process of accumulation of the content of nitrate, thus modifying the quality of forage crops. In samples of maize, alfalfa and fodder beet, cultivated by the using of worm compost, this indicator decreased respectively with 2.75% - 23.24%, in comparison with its value in plants of control lot. In the plants cultivated with the fund of the ammonium nitrate the content of these increased by 1.15-4.15 times, in comparison with its value in plants of control lot. Thus, it was evaluated the role of worm compost in the process of obtaining the qualitative forage crops by reduction the content of nitrate in them.